Soil Layer Destruction by Flat-Cutting Working Bodies - S. V. Belousov; V. B. Rykov; S. I. Kambulov; B. V. Turovsky (Сельскохозяйственные машины и технологии)
The paper emphasizes the importance of considering the dependence of soil tensile resistance on the relative moisture content when using flat-cutting working tools. Additionally; it highlights the dependence of soil tensile resistance on rhombic cross-section blades and the number of cutting planes. This study focuses on examining the effect of the blade sharpening angle on the specific cutting resistance of the fertile soil layer. (Research purpose) To study the soil layer destruction process using flatcutting working bodies. (Materials and methods) A new soil-tillage tool was developed and subjected to preliminary theoretical analysis. The experimental methodology focuses on measuring only the vertical component of the soil layer’s pressure acting on the working tool. Theoretical analysis demonstrates that the side brackets supporting the blade move along pre-designed guides. (Results and discussion) The research novelty lies in establishing relationships that describe the dependence between the parameters and operating modes of the new working body during its interaction with the soil. A method for the engineering calculation of the working body’s interaction with surfaces has been proposed. The findings indicate that; in heavy loam; the lowest resistance is achieved with a tine on the working organ width of 5 centimeters and a length of 7 centimeters when the ratio of the tine width to the distance between the tines is 2-3.5. (Conclusions) It has been established that the tine length should be approximately equal to the distance between the tines. The study also highlights the impact of sharpening on the technical condition of working bodies and the overall productivity of the tool. Analytical data indicate that for blades with a large cutting width; increasing the cutting depth is more effective in reducing specific cutting resistance.